Peningkatan Kreativitas Anak Melalui Media Plastisin Tepung Kelompok A TK AN Nur Hangtuah Perhentian Raja Kampar Tahun Ajaran 2017/2018 - Minarni Minarni; Mohammad Fauziddin; Melvi Lesmana (Jurnal Pendidikan Tuntas, 2023)
This research was conducted because of the low creativity of children in group A of An-Nur Hangtuah Kindergarten and this affects the overall learning process, therefore the researcher proposes an alternative problem solving in the form of learning with the help of flour plasticine media. The research method applied is a type of class room action research (PTK) with 4 stages, namely the planning stage, the implementation stage, the observation stage and the reflection stage. Data collection techniques used are observation techniques and documentation techniques, while data analysis techniques are quantitative data analysis techniques and qualitative data analysis techniques. The results of the study showed an increase in children's creativity through flour plasticine media activities in group A of An Nur Hangtuah Kindergarten Perhentian Raja Kampar Academic Year 2017/2018. Keywords: Creativity, Children, Plasticine media